Role of membrane cholesterol in differential sensitivity of muscarinic receptor subtypes to persistently bound xanomeline - Randáková, Alena; Dolejší, Eva; Rudajev, Vladimír; Zimčík, Pavel; Doležal, Vladimír; El-Fakahany, Esam E; Jakubík, Jan (Neuropharmacology, 2018)
Xanomeline (3-(Hexyloxy)-4-(1-methyl-1,2,5,6-tetrahydropyridin-3-yl)-1,2,5-thiadiazole) is a muscarinic agonist that is considered to be functionally selective for the M1/M4 receptor subtypes. Part of xanomeline binding is resistant to washing. Wash-resistant xanomeline activates muscarinic receptors persistently, except for the M5 subtype. Mutation of leucine 6.46 to isoleucine at M1 or M4 receptors abolished persistent activation by wash-resistant xanomeline. Reciprocal mutation of isoleucine 6.46 to leucine at the M5 receptor made it sensitive to activation by wash-resistant xanomeline. Lowering of membrane cholesterol made M1 and M4 mutants and M5 wild type receptors sensitive to activation by wash-resistant xanomeline. Molecular docking revealed a cholesterol binding site in the groove between transmembrane helices 6 and 7. Molecular dynamics showed that interaction of cholesterol with this binding site attenuates receptor activation. We hypothesize that differences in cholesterol binding to this site between muscarinic receptor subtypes may constitute the basis for xanomeline apparent functional selectivity and may have notable therapeutic implications. Differences in receptor-membrane interactions, rather than in agonist-receptor interactions, represent a novel possibility to achieve pharmacological selectivity. Our findings may be applicable to other G protein coupled receptors.
Keywords: inositolfosfáty; radioligandová zkouška; Calcium; Muscarinic Agonists; receptory muskarinové; Inositol Phosphates; vápník; Radioligand Assay; CHO Cells; Cholesterol; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Molecular Docking Simulation; Flow Cytometry; molekulární modely; agonisté muskarinových receptorů; Cricetulus; simulace molekulového dockingu; thiadiazoly; Cell Membrane; tritium; cholesterol; Models, Molecular; průtoková cytometrie; Animals; CHO buňky; Tritium; zvířata; buněčná membrána; pyridiny; Pyridines; Receptors, Muscarinic; Thiadiazoles